La pluralité des races humaines de G. Pouchet : l’imaginaire des discours scientifiques - Husti, Carmen (Studia Romanica Posnaniensia, 2018)
Being subject to interdisciplinary questioning in the nineteenth century, the human race appears in the text of the young scientist Georges Pouchet as an issue of the construction of a scientific method based on objectivity. Confronted with the limits of nineteenth-century geographical and ethnographic knowledge, this object of study proves that the plurality of human races is difficult to apprehend using objective scientific methods and experimentation, and reflects the imaginary present in the construction of scientific discourse.